Pengembangan Media Edmodo pada Model Pembelajaran Flipped Classroom di Masa Pandemi (Studi Materi Pokok Laju Reaksi) - Rezki, Nur Annisa; Hasri, Hasri; Anwar, Muhammad (Chemistry Education Review (CER), 2022)
This development research aims to develop an application-based learning media called the Edmodo application by adopting the Flipped Classroom learning model into learning to increase students' motivation and learning outcomes during the pandemic in Reaction Rate subject which is valid, practical, and effective. The development model used in this study referred to the Addie development model, which consisted of several stages, namely analysis, design, development, implementation, and evaluation. The Edmodo media developed had conducted through the validation stage by validators/experts and had gone through trials, and had been revised by developers so resulted a learning media which is valid, practical, and effective. The results show that the developed Edmodo media has: (1) the media expert validation by 3.96 with very valid criteria, (2) the material expert validation by 3.83 with very valid criteria. Edmodo media is stated to be practical because in the practicality test related to: (1) its implementation in the Flipped Classroom learning model is at an average value of M = 1.98 with the category of fully implemented, (2) the teacher's response is very positive with a percentage of 97.00% with very practical criteria, and (3) the students' responses are very positive with a percentage of 83.69% with very practical criteria. The media also met the effectiveness criteria with the results: (1) there is a difference in the average students’ learning motivation before and after the trial and (2) the learning outcomes meet the effective criteria with a class completeness percentage of 84%.